Implementation of Executorial Title Towards Auctions on Credit Guarantees for House Ownership as Reviewed from Law Number 4 of 1996 Concerning Mortgage Rights on Land and Objects Related to Land - Meutia, Irviana; Barus, Theresia Juliana Ngarakken; Maskanah, Ummi (Manunggal Halim Jaya, 2025)
The need for housing has now become mandatory. The credit scheme will make it easier for everyone to own a house by guaranteeing the legality of land rights burdened with mortgage rights. However, not everyone who has applied for credit always complies with the terms agreed in the Credit Agreement. One example is a debtor who breaks his promise or defaults by not paying installments so that the bank, as a creditor, confiscates the object of collateral. To pay the debtor’s remaining debt until repayment, the bank sells the collateral object belonging to the debtor by auction. The bank carries out this auction based on the executorial power attached to the Mortgage Rights Certificate so that the bank does not need to submit a request or lawsuit to the court because the executorial power of the Mortgage Rights Certificate is the same as a court decision with permanent legal force.